Sex-positive social work - Dodd, Sarah-Jane (Columbia University Press, 2020)
"Social workers engage with sex and sexuality in all kinds of practice settings and with a variety of client populations. However, conversations about healthy sexuality and sexual well-being are all but absent from social work literature, education, and practice. Many social work professionals have internalized sociocultural taboos about talking about sexuality and tend to avoid the topic in their practice. This book provides an overview of key sexuality-related topics for social workers from a sex-positive perspective, which encourages agency in sexual decision making and embraces consensual sexual activity as healthy and to be enjoyed without stigma or shame. It discusses a wide range of topics including physiology, sexual and gender identity, sex in older adulthood, BDSM and kink; nonmonogamous and polyamorous relationships, and ethical considerations, including erotic transference. The book is designed to embolden social workers to engage discussions of sexuality with clients and to provide an opportunity for self-reflection and professional growth. Accessible to students as well as social workers and mental-health professionals at all levels, Sex-Positive Social Work emphasizes the relationship between sexual well-being and overall well-being, giving social workers the tools to approach sex and sexuality actively and positively with clients. SJ Dodd is associate professor at the Silberman School of Social Work at Hunter College and the CUNY Graduate Center. She is also founding director of the Silberman Center for Sexuality and Gender. She is coauthor of Practice-Based Research: A Guide for Reluctant Researchers (2012)"--